Marketing de contenido como estrategia de posicionamiento del recurso turístico “Cascada 9 de Octubre” : Content marketing as a positioning strategy for the tourist resource "Cascada 9 de Octubre" - Mera Intriago, Kenia Michel (2024)
In this article we studied the impact of content marketing as a positioning strategy for the tourist resource "Cascada 9 de Octubre", located in the parish of San Isidro. Through the investigation, it was determined that the tourist destination has great growth potential, due to its position and the tourist service it offers, but it does not have an adequate promotion management, this is because they are unaware of the impact that marketing has. of content. The objective framed in developing an effective content marketing strategy based on the geographical reach and based on the content to position a tourist resource. Within the study, a descriptive analytical investigation was carried out, using a qualitative and quantitative inquiry, while the techniques that were used were a survey questionnaire and an observation sheet to be able to see, analyze the influence of this factor within the canton. San Isidro. For the processing of the information, the statistical program SPSS.v 26 was used, whose reliability was 0.89, the Cronbach's alpha coefficient. In conclusion, the research showed that a content marketing strategy would increase brand recognition, since most of the respondents answered that they view advertising through social networks, in addition to when they decide what type of tourist place to visit they look for information on the internet, to be able to identify which are the products and services that are offered in this way, managing to connect with the destination.